An Idealized Cloud-Resolving Modeling Study on Rainfall in Taiwan Under Uniform Northeasterly Flow in Winter, Part I: Effects of Wind Direction, Speed, and Moisture Amount - Chung-Chieh Wang; Chun-Hsien Li; Shin-Yi Huang; Chih-Sheng Chang (Atmosphere)
This study performs idealized simulations of rainfall in Taiwan in a winter monsoon regime under different wind direction (Wd; every 15° from 0° to 90°), speed (Ws; 12, 8, and 4 m s−1), and relative humidity (RH; 80, 70, and 60%) combinations at low levels, based on a simplified mean sounding profile from observations during the event over 20–24 November 2020. Thus, at a horizontal grid size of 2 km, a total of 7 × 3 × 3 = 63 runs are performed and the aim is to investigate the response in daily rainfall in northern Taiwan to these three parameters. The model results from the closest combination are verified against the observed rainfall both during the reference event and in several historical cases with reasonable agreement, indicating the usefulness of the approach, albeit with some limitations. From the experiments, our main findings can be summarized as below. First and foremost, with Ws = 12 m s−1 and RH = 80%, when the prescribed Wd changes from 0° (northerly) to 90° (easterly) gradually, the main rainfall areas shift from northern to northeastern Taiwan, with local maxima at the northern tip, northeastern tip of Taiwan, and near Suao (at the end of the Central Mountain Range) in response, indicating topographic uplifting for rainfall production. At a larger impinging angle, the Suao area tends to receive the most daily rainfall and can exceed 300 mm at Wd of about 75°–80°. Second, when Ws decreases to 8 m s−1, the general rainfall regions often remain similar but the amounts become lower, especially at local maxima. The peak amount near Suao is only about 100 mm. At weak wind of Ws = 4 m s−1, only moderate rainfall of 20 mm or below can be produced in Taiwan, and the local centers become not discernable. Third, when RH is lowered, the rainfall in northern Taiwan decreases significantly, especially along and near the coast under weaker winds coming from smaller angles. At RH = 70%, a higher accumulation (≥100 mm or so) near Suao is only possible with Wd ≥ about 55° at Ws = 12 m s−1 or when Wd ≥ 70° at Ws = 8 m s−1. At RH = 60%, the rainfall in northern Taiwan (and on the entire island) further decreases, again more evidently in cases with smaller Wd and Ws values.